Increasing Students' Understanding of Masbuk in Prayer Through the Use of YouTube Learning Videos - Nurdin (Al-Iftah: Journal of Islamic studies and society, 2024)
This study aims to enhance students' understanding of the "Masbuk in Prayer" material through the use of YouTube video-based learning media at MTs Maarif in Pinrang Regency. The Classroom Action Research (CAR) was conducted in two cycles, involving 25 students. The study focused on improving learning quality and outcomes through the integration of video-based media into the instructional process. The results indicate significant improvements in both cycles. In Cycle I, the average student score reached 75, with a mastery level of 64%, categorized as "sufficient." In Cycle II, the average score rose to 83, with a mastery level of 88%, categorized as "good." This increase demonstrates the effectiveness of YouTube videos in addressing gaps in understanding and fostering better engagement among students. The use of video media proved effective in enhancing several aspects of learning. Students exhibited increased active participation during class discussions, greater confidence in expressing opinions, and improved ability to summarize and organize information from video content. These improvements were attributed to the interactive nature of YouTube videos, which helped transform abstract concepts into concrete and relatable knowledge. The findings align with existing theories on the benefits of visual and audio-based learning media. Interactive video content facilitates better comprehension and retention of material, fostering analytical skills and deeper understanding. This study confirms that integrating YouTube video-based learning media can be an effective and efficient strategy for improving learning quality, particularly in Islamic jurisprudence topics such as "Masbuk in Prayer." This research highlights the importance of utilizing technology to create an engaging learning environment that aligns with the needs of Generation Z students, who are accustomed to visual and interactive learning tools. It emphasizes the role of educators in leveraging such media to achieve better learning outcomes.